New-onset refractory status epilepticus: Etiology, clinical features, and outcome. (3rd November 2015) - Gaspard, Nicolas; Foreman, Brandon P.; Alvarez, Vincent; Cabrera Kang, Christian; Probasco, John C.; Jongeling, Amy C.; Meyers, Emma; Espinera, Alyssa; Haas, Kevin F.; Schmitt, Sarah E.; Gerard, Elizabeth E.; Gofton, Teneille; et al.
Abstract : Objectives: The aims of this study were to determine the etiology, clinical features, and predictors of outcome of new-onset refractory status epilepticus. Methods: Retrospective review of patients with refractory status epilepticus without etiology identified within 48 hours of admission between January 1, 2008, and December 31, 2013, in 13 academic medical centers. The primary outcome measure was poor functional outcome at discharge (defined as a score >3 on the modified Rankin Scale). Results: Of 130 cases, 67 (52%) remained cryptogenic. The most common identified etiologies were autoimmune (19%) and paraneoplastic (18%) encephalitis. Full data were available in 125 cases (62 cryptogenic). Poor outcome occurred in 77 of 125 cases (62%), and 28 (22%) died. Predictors of poor outcome included duration of status epilepticus, use of anesthetics, and medical complications. Among the 63 patients with available follow-up data (median 9 months), functional status improved in 36 (57%); 79% had good or fair outcome at last follow-up, but epilepsy developed in 37% with most survivors (92%) remaining on antiseizure medications. Immune therapies were used less frequently in cryptogenic cases, despite a comparable prevalence of inflammatory CSF changes. Conclusions: Autoimmune encephalitis is the most commonly identified cause of new-onset refractory status epilepticus, but half remain cryptogenic. Outcome at discharge is poor but improves during follow-up. Epilepsy develops in most cases. The role of anesthetics and immune therapies warrants further investigation.